2018
DOI: 10.1016/j.meatsci.2018.06.035
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting lamb eating quality and the potential for their integration into an MSA sheepmeat grading model

Abstract: Major efforts in the sheep industry to control eating quality have resulted in reduced product variability. Yet inconsistent eating quality for consumers remains, due to a degree of inaccurate representation of cut quality. Eating quality defined through a complex interplay of different factors can be predicted for individual cuts, and Meat Standards Australia (MSA) grading schemes have been developed to achieve these defined quality outcomes. This review outlines the justifications to refine the current sheep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 77 publications
0
29
0
1
Order By: Relevance
“…Australian, Chinese, and United States consumers rated Australian lamb [57,189]. In general, consumers rated lamb loin and topside cuts similarly across countries, except for Chinese consumers, who rated topside cuts slightly lower in tenderness liking than Australian and United States consumers.…”
Section: Lamb Consumersmentioning
confidence: 85%
See 1 more Smart Citation
“…Australian, Chinese, and United States consumers rated Australian lamb [57,189]. In general, consumers rated lamb loin and topside cuts similarly across countries, except for Chinese consumers, who rated topside cuts slightly lower in tenderness liking than Australian and United States consumers.…”
Section: Lamb Consumersmentioning
confidence: 85%
“…They found that branched chain fatty acids of 4-methyloctanoic and 4-ethyloctanoic were related to consumer odor and overall liking attributes, but not to consumer flavor liking [187]. While other consumer studies have been conducted with Australian consumers and have reported a slight preference for grain-fed lamb [182,188], other drivers may influence consumer acceptance, such as frequency of consumption and environmental and health concerns [189].…”
Section: Lamb Consumersmentioning
confidence: 99%
“…Meat eating quality is influenced mainly by marbling, juiciness, tenderness and flavour [197]. Studies with lamb have shown that carcass intramuscular fat deposition and FA composition account for eating quality variation [198,199].…”
Section: Meat Eating Qualitymentioning
confidence: 99%
“…As in beef, the development of a sheep Meat Standards Australia (MSA) grading system is underpinned by sensory evaluations of vast numbers of untrained consumers [1][2][3]. The MSA prediction model forecasts consumer eating quality of a final cooked product, and is based on consumer scoring of a variety of muscles using descriptors of tenderness, juiciness, liking of flavour and overall liking [1,4].…”
Section: Introductionmentioning
confidence: 99%
“…The MSA prediction model forecasts consumer eating quality of a final cooked product, and is based on consumer scoring of a variety of muscles using descriptors of tenderness, juiciness, liking of flavour and overall liking [1,4]. This prediction model is successfully implemented for beef and is being developed for sheep [3]. While the merit of using untrained consumers is that they are by definition unbiased, some potential drawbacks can include high variance of consumer scores, and the risk of sampling from discreet sectors of the community not representative of an entire population.…”
Section: Introductionmentioning
confidence: 99%